Peptide Hp(2–20) accelerates healing of TNBS-induced colitis in the rat. Issue 9 (November 2018) - Gravina, AG; Prevete, N; Tuccillo, C; De Musis, C; Romano, L; Federico, A; de Paulis, A; D'Argenio, G; Romano, M
Background and aims: Hp(2–20), a Helicobacter pylori- derived peptide interacting with N-formyl peptide receptors (FPRs), accelerates the healing of gastric injury in rats. Whether Hp(2–20) affects the recovery of inflamed colonic mucosa is unknown. We evaluated whether Hp(2–20) accelerated the healing of 2, 4, 6-trinitrobenzenesulfonic acid (TNBS)-induced colitis and explored the mechanism(s) underlying any such effect. Methods: Fifteen rats underwent rectal administration of Hp(2–20) 250–500 µg/kg/day, or of its control peptide Hp1 for 10 days, following induction of colitis with TNBS. Macroscopic and histological damage was quantified using predetermined injury scores. FPR1, COX-2, TNF-α, TGF-β, HB-EGF and tissue transglutaminase ( t-TG ) messenger RNA (mRNA) expression in colonic tissue was determined by quantitative polymerase chain reaction; FPR1, TNF-α and COX-2 protein levels by Western blotting. Results: (1) Hp(2–20) accelerated healing of TNBS-induced colitis compared to controls consistently with the expression of FPRs in colonic mucosa; (2) TNBS upregulated mRNA mucosal expression of COX-2, TNF-α, TGF-β, HB-EGF and t-TG and (3) this, with the exception of HB-EGF, was significantly counteracted by Hp(2–20). Conclusions: Hp(2–20), an FPR agonist, accelerates the healing of TNBS-induced colitis in the rat. This effect is associated with a significant reduction in colonic tissue levels of COX-2, TGF-β, TNF-α and t-TG . We postulate that FPR-dependent pathways may be involved in the repair of inflamed colonic mucosa.